Anchor Establishment Factors: Phenomenological Study of the Rejection Towards Banking Payroll - Aad Satria Permadi; Faturochman Faturochman (ANIMA Indonesian Psychological Journal, 2015)
Muhammadiyah owns 16,346 kindergartens across Indonesia. In Yogyakarta, out of 212 kindergartens listed in the government, 70 belong to Muhammadiyah (30%). Cumulatively, distribution of money in Yogyakarta's Muhammadiyah kindergarten is significant; however none of the kindergartens use the banking payroll system, making it vulnerable to financial exploitation and corruption. There is a rejection towards this banking payroll system. The current study aims to understand the factors influencing such rejection. Qualitative approach used in the study was phenomenology. Results from in-depth interviews and focus group discussions (FGD) on five teachers showed that anchors were established through the dynamics of two factors: leadership experience and belongingness. Variations between the factors create a new layer of anchor. More participants are needed to better understand the forming of anchors, as well as statistical analysis to validate the new anchor.